CHARACTERISTICS OF SPORTS BRA PREFERENCES IN ADOLESCENT FEMALES. Issue 7 (30th July 2021) - Rizzone, Katherine H.; Edison, Bianca; Chung, Jane; Ichesco, Ingrid K.; Coleman, Nailah
Background: For many active females, a sports bra is an essential piece of equipment to comfortably participate in sports. Appropriately fitted, it allows the wearer to focus on the physical activity, rather than their body. While the number of young females participating in sports has continued to increase over recent decades, there is a paucity of literature on this important element of sports gear. Purpose: To characterize the usage and preferences of specific sports bra characteristics in an active female cohort Methods: This cross-sectional, multiceter survey study was conducted at five geographically distinct academic centers. The 19-item measure was administered via REDCap during sports medicine clinic visits. Face and content validity were established through iterative editing of the measure after feedback from area experts and a small sample of the targeted study cohort prior to initial administration. Females aged 13-22 were recruited. Chi-square and t-tests were utilized to assess differences between subgroups. Results: A total of 244 respondents completed the questionnaire. Mean age was 15.9 +/-2.8 years, 17.6% of the cohort was non-white and 10.3% identified as Latina. Mean BMI was 22.9 +/- 4.9, 25.8% were overweight and 11.9% were obese. The most common non-sports bra cup sizes were B (32.0%), A (17.3%) and C (17.3%). Nearly a fourth (23.7%) of the respondents reported that lack of bra support or breast discomfort had prevented them from exercising or being physically active. This was more commonly reported by those who were overweight (28.6%, BMI=25-29) or obese (37.9%, BMI>30) (p=0.08). Almost a quarter of white respondents reported breast discomfort preventing physical activity (23.6%); 20% of Black respondents and 32% of Latina respondents answered affirmatively to this question (p=0.11). Respondents that were bra size C or larger reported that their physical activity was negatively impacted by breast discomfort or lack of support 47.4% of the time, whereas only 15.8% of those with a bra size B or smaller reported the same (p<0.01). The most important factor in sports bra selection was amount of support (44.8%). Conclusions: Breast discomfort and lack of bra support may be an important barrier for young females of specific populations in meeting physical activity recommendations, which could lead to increased weight accrual, thus perpetuating the cycle of discomfort and lack of activity. Further research is needed to understand the issues related to sports bra preferences and usage to help inform future enhancement initiatives for this essential piece of sporting equipment.